KEBIJAKAN PEMERINTAH KOTA DUMAI DALAM PENGENDALIAN PENCEMARAN LINGKUNGAN DI KAWASAN PELABUHAN INDONESIA I CABANG DUMAI TAHUN 2013 (STUDI PADA KANTOR LINGKUNGAN HIDUP KOTA DUMAI) - Listiyani, Novita; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Industrial growth give the positive impact for example in the form of state's stockexchange increase, transfer the technology and labour absorbtion. But that way, besides givingimpact which are positive in the reality growth of industrial sector also give the negative impact,so that development which is with vision of environment failed to come into. So needing of theenvironmental control of contamination pursuant number 32 Year 2009 about protection andenvironment management. Area of Port of Indonesia I Branch the Dumai not only just factorystanding, but still a lot of resident settlement which live in about factory, they can easily incuredimpact from industrial activity like as smoke, waste, and other environmental damage which canharm the resident. One of them which is often happened by event of falled Crude Palm Oil(CPO) in sea Dumai by repeatedly, meaning Standard of Operational and Procedure (SOP)industrial CPO to applying of standard of transportation CPO ill defined port.This research in Office of Environment of Town Dumai and in Area of Port of Indonesia IBranch the Dumai. As for theory used by concerning Public Policy. this Research Method isresearch qualitative, while technique of data collecting is documentation and interview. Whiledata analysis descriptively. This research study the effort of execution of Local Government ofTown Dumai in environmental control of contamination in area of Pelindo I Branch the Dumaiand factors influencing environmental control of contamination execution in area of Pelindo IBranch Dumai. Environmental control of contamination in area of Pelindo I Branch the Dumaiis socialization, observation and publisher. Although have been various action, but there be stillinterpose to all industrial perpetrator the environmental contamination in area of Pelindo IBranch Dumai.Key Word: Policy, Local Government, Environmental Control Of Contamination, Area OfPort Of Indonesia I Branch Dumai.